Characteristics and outcomes of hospitalised patients with vertebral fragility fractures: a systematic review - Ong, Terence; Kantachuvesiri, Pitchayud; Sahota, Opinder; Gladman, John R.F. (Oxford University Press, 2018)
Background: The complex management for patients presenting to hospital with vertebral fragility fractures provides justification for the development of specific services for them. A systematic review was undertaken to determine the incidence of hospital admission, patient characteristics, and health outcomes of vertebral fragility fracture patients to inform the development of such a service.